Modelo de Tecnologías de Información para la captación del talento deportivo en centros escolares peruanos - Laredo-Montero, Arturo (2020)
This research entitled "Information Technology Model for attracting sports talent in Peruvian schools” stems from the need, by state institutions, for an information technology tool that helps competent entities to improve in the capture of human skills in sports activities and that schools in Peru lack this instrument. It is for this reason, that not all talents are captured and those who are recruited, for the most part, are recruited by factors of luck or their own will. This research was carried out under the qualitative and quantitative approach with a descriptive scope, where instruments such as interviews and observation were applied to trainers, physical education teachers, as well as professional personnel involved in sports management. As a product of this study, it has been possible to outline an Information Technology model that allows the integration and development of sports talent through competitive indicators to measure their skills and abilities, which will allow to verify if the captured athlete has the sporting ability to compete in Future international tournaments and significantly reduced defection and loss of talent.